The effect of the major jurisprudence rule matters with their purposes and the rule of consideration for purposes and meanings, not for the words and premises included under them in the Saudi Code of Criminal Procedure - Albediwi, Aisha Ahmed (Journal of Islamic Sciences, 2022)
The research aimed at demonstrate the fruit of the science of jurisprudence, and to reveal the extent of the abundance of Islamic jurisprudence and its containment of all the problems that appear in the developments of the times, including the Saudi systems. And with what came with the jurisprudential rules and controls that are originally considered one of the foundations of reference for the rules of the system, and in linking the rules and the system, it gives the system more acceptance and ease of application, and transfers the rules and regulations of jurisprudence from the theoretical side to the applied side, and one of the important jurisprudential rules is the major jurisprudential rule (Matters with their purposes) and their importance is represented by the multiplicity of their applications in worship, transactions and crimes, which have a clear and evident impact in real life and the developments of the times. In addition to the impact of the rules included in it, which is the rule of consideration for purposes and meanings, not for words and premises.